DESIGNING LEARNING TRAJECTORY OF SET THROUGH THE INDONESIAN SHADOW PUPPETS AND MAHABHARATA STORIES - Irma Risdiyanti; Rully Charitas Indra Prahmana (IKIP Siliwangi and I-MES, 2021)
Indonesia has many cultures that can be used as a starting point in learning mathematics. Yet, many teachers still use conventional methods to provide explicit mathematical content without connecting with students' culture and daily activities. One of the learning approaches that can solve these problems is Realistic Mathematics Education (RME). This approach uses context as one of its characteristics containing students' culture and their daily activities. On the other hand, Wayang (Indonesian shadow puppets) and Mahabharata stories have the characteristics that can be a context in the learning of set. This research aims to design the Hypothetical Learning Trajectory (HLT) of the set using the RME approach through Wayang and Mahabharata stories, which are familiar with students' culture in Yogyakarta. This HLT will then be tested on students in further research until it becomes the Local Instructional Theory (LIT) on set. Students can study about set by grouping Wayang in Mahabharata stories based on their characters. The research result is the HLT of set through the context of wayang and Mahabharata stories containing learning goals, learning activities, and the conjecture of every activity. This HLT can be a promising solution to overcome students' difficulties in understanding the concept of sets and values in the cultural context to improve the students' character.